Solution of Fractional Differential Equations: Transform and Iterative Methods Approach - Alchikh, Razan Abdul Satar (2019)
A Master of Science thesis in Mathematics by Razan Abdul Satar Alchikh entitled, “Solution of Fractional Differential Equations: Variational Iteration Approachs”, submitted in December 2019. Thesis advisor is Dr. Suheil Khoury. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).